2014
DOI: 10.1021/es405807w
|View full text |Cite
|
Sign up to set email alerts
|

Polyacrylonitrile-Chalcogel Hybrid Sorbents for Radioiodine Capture

Abstract: Powders of a Sn2S3 chalcogen-based aerogel (chalcogel) were combined with powdered polyacrylonitrile (PAN) in different mass ratios (SnS33, SnS50, and SnS70; # = mass% of chalcogel), dissolved in dimethyl sulfoxide, and added dropwise to deionized water to form pellets of a porous PAN-chalcogel hybrid material. These pellets, along with pure powdered (SnSp) and granular (SnSg) forms of the chalcogel, were then used to capture iodine gas under both dynamic (dilute) and static (concentrated) conditions. Both SnS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
91
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(92 citation statements)
references
References 36 publications
1
91
0
Order By: Relevance
“…In recent years, adsorption onto a porous adsorbent has been the primary choice for the removal of radioactive iodine gas due to its advantages that include reliability, simplicity and low operating costs [7]. Previously, several sorbents has been investigated to trap the iodine which includes activated carbon [8,9], silver-exchange zeolite [10], AgNO 3 -impregnated silica and alumina [11,12], silver-functionalized silica aerogels [13], silver-exchanged titania (ETS-10) [14], chalcogen-based aerogel [15][16][17][18], monolithic aerogels of polymeric organic framework [19], and metal organic frameworks [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, adsorption onto a porous adsorbent has been the primary choice for the removal of radioactive iodine gas due to its advantages that include reliability, simplicity and low operating costs [7]. Previously, several sorbents has been investigated to trap the iodine which includes activated carbon [8,9], silver-exchange zeolite [10], AgNO 3 -impregnated silica and alumina [11,12], silver-functionalized silica aerogels [13], silver-exchanged titania (ETS-10) [14], chalcogen-based aerogel [15][16][17][18], monolithic aerogels of polymeric organic framework [19], and metal organic frameworks [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Silver ion-exchange adsorbent with 10 wt% silver showed effective removal of methyl iodide at high temperature (380°C). Riley et al [15][16][17] and Subrahmanyam et al [18] synthesized chalcogen-based aerogels, polyacrylonitrile-chalcogel hybrid and chalcogenide as sorbents for remediation of radioactive iodine, respectively. Zeng et al [20] synthesized Zn-lactate connected by organic group (pybz) forming the double walls, which showed higher I 2 affinity as compared to zeolite 13X and activated carbon.…”
Section: Introductionmentioning
confidence: 99%
“…Long‐term isolation of 129 I is critical for safe disposal of nuclear waste because of the presence of 129 I in nuclear fuel reprocessing waste streams, and its long radioactive half‐life of 15.7 million years. Consequently, the effective separation, capture, and storage of 129 I, and other gas phase radionuclides, are areas of active research and regulation . Silver‐containing zeolites, in particular Mordenite (MOR), have historically been considered for removing 129 I 2 from gas phase nuclear waste streams .…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the effective separation, capture, and storage of 129 I, and other gas phase radionuclides, are areas of active research and regulation. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Silver-containing zeolites, in particular Mordenite (MOR), have historically been considered for removing 129 I 2 from gas phase nuclear waste streams. 16 Yet only recently has the molecular basis for zeolite performance been established through structure-property analyses.…”
Section: Introductionmentioning
confidence: 99%
“…The higher iodine sorption capacity observed in graphene aerogel at relatively lower specific surface area was attributed to the pore shape and size of the highly porous graphene aerogel. The activation energy of iodine sorption was calculated to be 70.63 kJ mol -1 at 298 -343 K. Riley et al[60][61][62] and Subrahmanyam et al[63] reported upon chalcogen-based aerogels, polyacrylonitrilechalcogel hybrid and chalcogenide sorbents for the remediation of radioactive iodine,…”
mentioning
confidence: 99%